2nd AeU Convocation, 22 April 2012, Kuala Lumpur - Asia e University, AeU (AeU, 2012)
The 2nd Convocation ceremony was held on Sunday 22nd April 2012 over 2 sessions at the Dewan Tun Dr. Ismail, Putra World Trade Centre, Kuala Lumpur. A total of 511 students graduated with various AeU degrees.